Facile Co3O4 nanoparticles deposited on polyvinylpyrrolidine for efficient water oxidation in alkaline media. Issue 12 (23rd September 2021) - Mugheri, Abdul Qayoom; Tahira, Aneela; Aftab, Umair; Nafady, Ayman; Vigolo, Brigitte; Ibupoto, Zafar Hussain
Abstract: To develop an inexpensive, earthabundant, efficient, and stable catalyst is very crucial for the realization of renewable energy for practical applications, but it is a difficult task. In this research study, we have deposited Co3 O4 nanoparticles on polyvinylpyrrolidine (PVP) through electro‐spun technique followed by carbonization. The structure and composition studies were carried by scanning electron microscopy, energy‐dispersive spectroscopy, and powder X‐ray diffraction techniques. The Co3 O4 nanoparticles are deposited on the nanofibers of PVP with improved surface area and conductivity; therefore, the hybrid material has shown an excellent oxygen evolution reaction (OER) in alkaline media. The onset potential for the presented OER catalyst is about 1.46 V versus reversible hydrogen electrode, and an overpotential of 280 mV is needed to reach a current density of 10 mAcm −2 . The Co3 O4 nanoparticles are highly durable for 20 hr and very stable. The low charge transfer resistance of 29.23 Ω is offered by the Co3 O4 hybrid material, which facilitated the OER kinetics in alkaline media. These obtained OER results may be utilized for the overall water splitting and the synthetic strategy is low cost, thus it favors the mass production of functional materials for diverse electrochemical applications. Abstract : Synthesis of process of Co3 O4 nanoparticles deposited on polyvinylpyrrolidine and their structural and water oxidation characterization.